Targeting Gut Bacteria Using Inulin‐Conjugated Mesoporous Silica Nanoparticles. Issue 14 (17th April 2022) - von Baeckmann, Cornelia; Riva, Alessandra; Guggenberger, Patrick; Kählig, Hanspeter; Han, Seung Won; Inan, Deniz; Del Favero, Giorgia; Berry, David; Kleitz, Freddy
Abstract: To facilitate the creation of novel nanocarrier systems targeting the intestinal microbiome, inulin‐conjugated mesoporous silica nanoparticles (MSNs) are described herein for the first time. Surface functionalization is achieved on either hydrophilic or hydrophobic mesoporous nanoparticles using different conjugation methods. The targeting performance of the resulting materials is assessed and compared upon incubation with human stool. It appears that amide formation is the most favorable coupling method on hydrophilic MSNs to achieve the desired bioconjugate. Remarkably, high affinity of gut bacteria to the conjugated particles can be obtained, paving the way to novel targeted drug delivery systems. Abstract : The formation of a bioconjugate using inulin and hydrophilic or hydrophobic mesoporous silica nanoparticles is developed. The targeting performance to inulin‐adherent gut bacteria of the resulting materials is assessed using human stool. High affinity of the bacteria for the conjugated particles can be obtained, enabling future targeting drug delivery systems.